Generation of dislocation glide loops in Czochralski silicon - Giannattasio, A; Senkader, S; Falster, R; Wilshaw, P (2002)
Critical stresses necessary to generate dislocation glide loops in Czochralski silicon containing oxide precipitates have been investigated. Using three-point bending and etching techniques, it was possible to determine the minimum shear stress required to generate dislocation glide loops from controlled distribution of precipitates under constant-stress conditions. The generation of glide dislocations was investigated in samples with different oxide precipitate sizes and different numbers of dislocations initially attached to precipitates. It has been found that the value of the critical resolved shear stress for generating dislocation glide loops depends on the duration of the applied stress. A qualitative model involving punched-out presmatic loops was considered for the explanation of the experimental data. It was found that glide dislocations must be generated from pre-existing large loops probably associated with particular oxide precipitates or other complex defects.